2010
DOI: 10.1007/978-90-481-9852-8_1
|View full text |Cite
|
Sign up to set email alerts
|

Plant Uptake of Xenobiotics

Abstract: Plant uptake of organic chemicals is an important process when considering the risks associated with land contamination, the role of vegetation in the global cycling of persistent organic pollutants, the potential for contamination of the food chain and the design of pesticides. There have been some significant advances in our understanding of the processes of plant uptake of organic chemicals in recent years; most notably there is now a better understanding of the air to plant transfer pathway, which may be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 63 publications
1
29
1
Order By: Relevance
“…Translocation of organic compounds within plants generally decreases with increasing hydrophobicity (Trapp and Legind, 2011). Also, roots have higher lipid content than most other plant tissues, and neutral compounds have been shown to be preferentially distributed in tissues with high lipid content (Collins et al, 2011). In addition, the rapid conversion of 14 C residue to the non-extractable form, as discussed above, may be another important factor for the negligible transfer from roots to other plant tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Translocation of organic compounds within plants generally decreases with increasing hydrophobicity (Trapp and Legind, 2011). Also, roots have higher lipid content than most other plant tissues, and neutral compounds have been shown to be preferentially distributed in tissues with high lipid content (Collins et al, 2011). In addition, the rapid conversion of 14 C residue to the non-extractable form, as discussed above, may be another important factor for the negligible transfer from roots to other plant tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Biodistribution Emerging contaminants Reclaimed water Recent research investigating the uptake of contaminants of emerging concern into plants from reclaimed irrigation water [27][28][29] has revealed conflicting ideas on how best to describe and predict how these emergent chemicals will enter and be distributed within a particular plant [16,18,21,23,24,[29][30][31][32][33][34][35][36][37][38][39]. Traditional models of organic contaminant uptake in plants suggested that compounds that were too hydrophobic would not undergo significant passive transport in the transpiration stream [21,40].…”
Section: Abstract: Bioaccumulationmentioning
confidence: 99%
“…The existence of conflicting models describing uptake of water soluble contaminants necessitates further examination of the preexisting assumptions and concepts [20][21][22][23]. For example, hydrophobic and neutral organic chemicals are known to accumulate in plant roots; some anionic pharmaceuticals have been shown to accumulate in alfalfa leaves from reclaimed irrigation water [24], and the behavior of some ionic and zwitterionic compounds was found to be governed by their hydrophobicity [12][13][14][25][26][27].…”
Section: Introductionmentioning
confidence: 99%